TCP Vegas end to end congestion avoidance on a global Internet. - Brakmo, L.S (IEEE Journal on selected areas in communications)
Vegas is an implementation of TCP that achieves between 37 and 71% better throughput on the Internet, with one-fifth to one-half the losses, as compared to the implementation of TCP in the Reno distribution of BSD Unix. This paper motivates and describes the three key techniques employed by Vegas, and presents the results of a comprehensive experimental performance study, using both simulations and measurements on the Internet, of the Vegas and Reno implementations of TCP